Efficiency of Inhaled Cannabidiol in Cannabis Use Disorder: The Pilot Study Cannavap - Cleirec, Grégoire; Desmier, Esther; Lacatus, Cristina; Lesgourgues, Simon; Braun, Anais; Peloso, Claire; Obadia, Chanaëlle (Frontiers in Psychiatry, 2022)
Introduction. There is currently no specific pharmacological treatment for cannabis use disorder (CUD). Cannabidiol (CBD) is the second most prevalent cannabinoid found in cannabis and is considered to be safe for use. Studies suggest that CBD may be of benefit in treating CUD. In clinical practice, CBD is already being used by patients who are trying to reduce their cannabis consumption or stop using cannabis entirely. The aim of this study was to assess the potential of CBD inhaled using a vaping device in CUD. Methods. This was an exploratory, observational, non-randomised, open-label study conducted at an Addiction Support and Prevention Centre in Paris. The primary endpoint was a reduction of at least 50% in the reported number of joints consumed daily at 12 weeks. The participants were given an electronic cigarette at the start of the study, along with liquid containing CBD. Nicotine at 6 mg/ml could be added in case of co-consumption of tobacco. They were assessed once a week and the CBD liquid dose was adjusted based on withdrawal signs and cravings (33.3 mg/mL, 66.6 mg/mL or 100 mg/mL). Results. Between November 2020 and May 2021, 20 patients were included and 9 (45%) completed the follow-up. All of the participants used tobacco, and were provided a liquid with nicotine. At 12 weeks, 6 patients (30% of the participants) had reduced their daily cannabis consumption by at least 50%. The mean number of joints per day was 3, compared to 6.7 at baseline. The mean amount of CBD inhaled per day was 215.8 mg. No symptomatic treatment for cannabis withdrawal was prescribed. Mild adverse effects attributable to CBD and not requiring the prescription of any medicines were reported in a few patients. Conclusion. This research provides evidence in favour of the use of CBD in CUD. It also illustrates the benefits of inhalation as the route of CBD administration in patients who use cannabis: inhalation can allow users to self-titrate CBD based on their withdrawal symptoms and cravings. A double-blind, randomised, multi-centre, placebo-controlled clinical trial is still needed to assess the efficacy of inhaled CBD in CUD.